Effects of Pyriproxyfen on Life Table Indices of Plutella xylostella in Multigenerations - Mohammad Mahmoudvand; Saeid Moharramipour; Mehrdad Iranshahi (Psyche: A Journal of Entomology)
The diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae), is a major pest of Brassicaceae family in Iran. This study investigated the sublethal effects of pyriproxyfen, a juvenile hormone analogue, on DBM, for two subsequent generations. The leaf dip bioassay method was adopted in conducting this experiment. Sublethal concentrations resulted in a significant decrease in fecundity, oviposition period, and pupal weight of parents and offspring generations. Also, the development time of DBM was prolonged after exposure to pyriproxyfen. The biological parameters such as net reproductive rate (R0) and intrinsic (rm) and finite (λ) rate of increase were lower than control in treatment groups, significantly. From our investigations, pyriproxyfen is a good choice for control of the diamondback moth population through continuous generations.